2017
DOI: 10.21608/jenvbs.2017.1550.1009
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Nanoremediation under Changing Climate

Abstract: MANY global problems threaten our life on the Planet including climate changes, environmental pollution, food and soil security, energy crisis, etc. This environmental pollution has not only mainly serious risks and stress involving the human health and safety of the entire ecosystem but also the quantity and quality of crops productivity worldwide. Due to the great gap between the global food production and the global consumption, there is a crucial need to cultivate these contaminated lands sooner or later. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 114 publications
0
1
0
Order By: Relevance
“…48 Previous work has demonstrated that particles larger than 20 nm face limitations due to pore size restrictions. [49][50][51] Thus, small particle nanomaterials with good dispersion are more easily absorbed. Furthermore, it has been concluded that negatively charged ions exhibit higher absorption and transport rates.…”
Section: Uptake and Translocation Of Ce-cdsmentioning
confidence: 99%
“…48 Previous work has demonstrated that particles larger than 20 nm face limitations due to pore size restrictions. [49][50][51] Thus, small particle nanomaterials with good dispersion are more easily absorbed. Furthermore, it has been concluded that negatively charged ions exhibit higher absorption and transport rates.…”
Section: Uptake and Translocation Of Ce-cdsmentioning
confidence: 99%
“…Nonoet al 2015 andMosaet al 2017). Abdel-Sabour et al (1996), Hassan et al (2013), Ali et al (2016), Ibrahim et al (2016), El-Ramady et al (2017) and Farid et al (2019) reported that sewage effluent has been used for crop irrigation for many years and its use is increasing particularly in water-short areas. Sewage effluent can be a useable water resource if suitable precautions are taken.…”
Section: Introductionmentioning
confidence: 99%